2022
DOI: 10.1108/mbe-06-2021-0073
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of supply chain agility on operational performances-a PLS-SEM approach

Abstract: Purpose This study aims to examine the effect of supply chain agility (SCA) on operational performance (OP) measurements of steel manufacturing firms. It also investigates the role of cost efficiencies concerning enhance OPs. Design/methodology/approach The study is based on an experimental research design by collecting data from responses 398 responses of key officials of India’s steel manufacturing firms. Analyses are carried to explore this modern concept with the help of Smart-partial least square (PLS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 141 publications
(230 reference statements)
4
11
0
Order By: Relevance
“…This result also supports Panigrahi, et al (2022), who suggest that SCA exemplifies one of its successful techniques in the unpredictable and competitive today's market. Additionally, they also argue that the development of SCA is a crucial strategy to increase satisfaction levels and establish a distinct market dominance (Panigrahi et al, 2022). Furthermore, SCA is also proven to have the function of mediating the effect of SCF on SMEs' performance.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This result also supports Panigrahi, et al (2022), who suggest that SCA exemplifies one of its successful techniques in the unpredictable and competitive today's market. Additionally, they also argue that the development of SCA is a crucial strategy to increase satisfaction levels and establish a distinct market dominance (Panigrahi et al, 2022). Furthermore, SCA is also proven to have the function of mediating the effect of SCF on SMEs' performance.…”
Section: Discussionsupporting
confidence: 84%
“…Chan et al (2017) found that organizational performance increases with an improvement in SCA. The same results were found in other studies where SCA has a role in competitively improving business performance (Panigrahi, et al, 2022;Jermsittiparsert, 2022;Swafford et al, 2008).…”
Section: Literature Reviewsupporting
confidence: 89%
See 2 more Smart Citations
“…The agility of a firm's SC refers to its capacity to respond rapidly to consumer needs while also maintaining costs in check (Golgeci et al 2019); these requirements can only be achieved using advanced digital technology. Panigrahi et al (2022) examined the relationship between SCA and operational performance in India. A strong relationship between agility in the SC and operational performance development has been improved.…”
Section: Literature Reviewmentioning
confidence: 99%